BRICS joint financial architecture: The New Development Bank - Luciana Acioly da Silva (Institute for Applied Economic Research (ipea), 2019)
The present text aims to analyze the New Development Bank (NDB) established by BRICS as part of the group's financial architecture, focusing on the main motivations for its creation, ways of acting and governance structure. Although focused on providing credit for infrastructure and sustainable development projects and acting through different practices of financial institutions established after the Second World War, NDB still faces important challenges to meet those goals.
Keywords: G15; G24; F55; 330; financial institutions; international capital markets; multilateral development banks; international lending; emerging markets; international institutional arrangements